Mapping Conflicts Involving Local Communities In Tourism Destinations: A Systematic Literature Review - Sevtiani, Masroulina; Abdullah, Taufik (Journey : Journal of Tourismpreneurship, Culinary, Hospitality, Convention and Event Management, 2025)
Tourism as a strategic sector often brings paradoxical consequences for local communities: on the one hand it promises economic growth, but on the other hand it triggers various social, cultural, spatial and environmental conflicts. This study aims to map conflicts involving local communities in tourism destination development through a systematic literature review approach of international academic publications. The results of the thematic analysis identified five main conflict categories: (1) conflict and resistance analysis, (2) perceptions, attitudes, and responses, (3) conflicts due to tourism development, (4) conflict resolution, (5) identity issues, and (6) online resistance. This study fills the gap in the literature by developing a classification of conflicts based on actors and issues, and highlighting forms of community resistance, both overt and symbolic. The findings reinforce the urgency of tourism planning based on social justice and inclusive participation for long-term sustainability.